1998
DOI: 10.1099/0022-1317-79-8-1977
|View full text |Cite
|
Sign up to set email alerts
|

A putative human papillomavirus type 57 new subtype isolated from plantar epidermoid cysts without intracytoplasmic inclusion bodies.

Abstract: Human papillomavirus type 60 (HPV-60) is the only virus type that has been identified in epidermoid cysts. In this study, HPV-57 DNA was found in three out of 18 plantar epidermoid cysts with different histological features from HPV-60-associated cysts, using PCR and Southern hybridization. The HPV-57-associated cysts had features resembling an HPV-2-specific cytopathic effect. The sequences of two HPV-57 DNA clones isolated from two patients were identical, but differed at some positions from those of HPV-57a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 20 publications
0
23
0
Order By: Relevance
“…4), cloning and sequencing of the DNA fragments [19]revealed that they were not from HPV DNAs but from cellular DNAs (data not shown).…”
Section: Case Reportmentioning
confidence: 99%
See 1 more Smart Citation
“…4), cloning and sequencing of the DNA fragments [19]revealed that they were not from HPV DNAs but from cellular DNAs (data not shown).…”
Section: Case Reportmentioning
confidence: 99%
“…To determine the causative HPV type, PCR was performed using not only a broad-spectrum PCR assay, amplifying most common skin as well as mucosal types of HPV [17]but also primers specific for HPV-2, -4, -27, -57, -60, -63 or -65 as described elsewhere [18, 19]. Primer pairs used to detect HPV-4, -63 or -65 were newly designed for this study from the L1 region of each HPV type (table 1).…”
Section: Case Reportmentioning
confidence: 99%
“…DNA sequencing was performed as mentioned previously [6]with our frozen specimen separately stored at –80°C. PCR products were cloned into pBluescript (Stratagen, USA) vector using the TA cloning method.…”
Section: Case Reportmentioning
confidence: 99%
“…They putatively labeled this HPV 57 ‘subtype c’. In our patient, we cloned viral DNA from a plantar epidermoid cyst and compared it with HPV 57a [2], 57b [3]and 57c [6]. The DNA sequence was almost identical to HPV 57c.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation